The comparison of direct magnetic resonance arthrography with volumetric interpolated breath-hold examination sequence and multidetector computed tomography arthrography techniques in detection of talar osteochondral lesions - Berhan Pirimoglu; Hayri Ogul; Gokhan Polat; Mecit Kantarci; Akin Levent (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to compare additive diagnostic values of magnetic resonance (MR) arthrography with volumetric interpolated breath-hold examination (VIBE) sequence and multidetector computed tomography (MDCT) arthrography for diagnosis and grading of talar osteochondral lesions. Methods: MDCT arthrography and MR arthrography with three dimensional VIBE sequence were performed in 27 patients. Findings of MR arthrography and MDCT arthrography images were compared with arthroscopic findings. Sensitivity, specificity, and accuracy rates were calculated for both MR arthrography and MDCT arthrography imaging findings. Results: For grade I osteochondral lesions; sensitivity, specificity and accuracy rates of MR arthrography were 95%, 73%, 90%, respectively; For grade I osteochondral lesions; sensitivity, specificity and accuracy rates of MDCT arthrography were 96%, 79%, 81%. For grade IV osteochondral lesions; sensitivity, specificity and accuracy rates of MDCT arthrography and MR arthrography were 100%. For grade II lesions, the sensitivity, specificity and accuracy rates of the MR arthrography were 80%, 76%, 77%, respectively; for grade III lesions, the sensitivity, specificity and accuracy rates of the MR arthrography were 78%, 68%, 75%. For grade II osteochondral lesions; the sensitivity, specificity and accuracy rates of the MDCT arthrography were 91%, 81%, 86%; for grade III osteochondral lesions; the sensitivity, specificity and accuracy rates of the MDCT arthrography were 90%, 83%, 89%; For grade II and III osteochondral lesions, MDCT arthrography had higher sensitivity, specificity and accuracy rates than MR arthrography. MDCT arthrography had higher diagnostic performance than MR arthrography for detection of grade II and III lesions (p = 0.041 and p = 0.038, respectively). Conclusion: MDCT arthrography appears to be more reliable than MR arthrography with three dimensional VIBE sequence for accurate detection and grading of osteochondral lesions. Level of evidence: Level III, Diagnostic Study. Keywords: Osteochondral lesion, Computed tomography, Arthrography, Ankle, Magnetic resonance imaging